Robust and secure authentication protocol protecting privacy for roaming mobile user in global mobility networks. (1st January 2021) - Madhusudhan, R.; Suvidha, K.S.
With the advent of new 5G technology there is a need to develop security architecture. Two factor authentication schemes are developed to address the security features such as user anonymity and privacy preservation during roaming scenario in GLObal Mobility NETwork. The entire communication during roaming is carried over insecure channel and owing to this, security concern is raised. The main objective of the proposed protocol is to secure the channel and to overcome all active and passive security attacks. The proposed protocol addresses the active and passive security attacks that exist in 5G cellular networks which are formally verified using AVISPA tool. The proposed protocol is simulated using NS2.35 simulator and the performance metrics such as throughput, end to end delivery and packet delivery ratio are computed. The protocol is efficient in terms of computational and communication cost. The proposed scheme is robust and practically implementable.